The effect of retinoic acid in the ability of cold solid thyroid nodule to take up radioactive iodine: A preliminary study - Andreas Lim; Hendra Budiawan; Budi Darmawan; Basuki Hidayat; Hadyana Sukandar; Achmad Hussein Sundawa Kartamihardja (World Journal of Nuclear Medicine)
One of the treatment options for benign thyroid nodules is radioactive iodine (RAI). However, this treatment is more effective for hot/warm solid thyroid nodules. Cold thyroid solid nodules are characterized by the lack of iodine uptake compared to normal thyroid tissue. Oral retinoic acid (RA) is a synthetic derivative of Vitamin A. The effect of RA on the uptake of RAI is still controversial. The aim of this study was to evaluate the effect of RA in the ability of a cold solid thyroid nodule to take up RAI. Individuals with a cold solid thyroid nodule based on ultrasonography and thyroid scintigraphy were included. Participants with liver dysfunction, smokers, and pregnant patients were excluded from the study. Each participant underwent thyroid uptake scintigraphy twice (pre- and post-RA consumption) using 35–37 MBq NaI-131. Participants consumed RA at a dose of 1 mg/kg body weight (BW) followed with 1.5 mg/kg BW. This study was approved by Dr. Hasan Sadikin General Hospital Ethic Committee. A total of 12 cold thyroid solid nodules were evaluated. The mean percentage of the nodule uptake value pre- and post-intervention was 1.11% and 0.62%, respectively (P = 0.004), while normal thyroid tissue uptake values pre- and post-intervention were 27.57% and 13.40%, respectively (P = 0.002). The percentage alteration of nodules and normal thyroid tissue uptake value were 42.4% and 51.5% lower, respectively (P = 0.354). This study showed that RA reduces the ability of cold solid thyroid nodule, as well as normal thyroid tissue, to take up RAI.